A mixed integer programming model for forest harvest scheduling problem. (March 2019) - Efratani Damanik, Sarintan; Purwoko, Agus; Hidayat, Rahmat
Abstract: The Forest Harvest Scheduling Problem (FHSP) and forest planning problems in general are combinatorial optimization problems. Briefly, the problem is to develop a forest management plan for a large area of forest satisfying multiple constraints and balancing competing objectives. Traditionally, mathematical programming has been and still is the most widely used technique for solving such problems. For the general forest harvesting problem, there exist a number of LP and MIP models. This paper study a restricted version of the the FHSP, called the Clear-cut Scheduling Problem (CCSP) as a test case. We attempt to model and to solve the CCSP using a MIP model. We will not model the problem as a LP since the literature survey shows that LP-based strategies are difficult to interpret and may be impossible to implement, largely due to their inability to express spatial relationships.